2009
DOI: 10.4049/jimmunol.182.1.563
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cytokine Production by Human Neutrophils Involves C/EBP Transcription Factors

Abstract: A growing number of neutrophil-derived cytokines have proven to be crucial to various inflammatory and immune processes in vivo. Whereas C/EBP (CCAAT/enhancer-binding protein) transcription factors are important for neutrophil differentiation from myeloid precursors, we report herein that they also regulate cytokine production in mature neutrophils. All known C/EBP proteins but C/EBP␥ are expressed in neutrophils; most isoforms localize to the nucleus, except for C/EBP␣, which is cytoplasmic. Neutrophil stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
67
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 56 publications
(72 reference statements)
8
67
1
1
Order By: Relevance
“…shown that C/EBP␤ plays an important role in regulating inflammatory responses in many different cell types (40,41). Similar to adipose tissue, the liver from WT mice on HFD showed a doubling of C/EBP␤ protein expression ( Fig.…”
Section: C/ebp␤ Controls Pro-inflammatory Gene Expression and Insulinmentioning
confidence: 88%
“…shown that C/EBP␤ plays an important role in regulating inflammatory responses in many different cell types (40,41). Similar to adipose tissue, the liver from WT mice on HFD showed a doubling of C/EBP␤ protein expression ( Fig.…”
Section: C/ebp␤ Controls Pro-inflammatory Gene Expression and Insulinmentioning
confidence: 88%
“…Importantly, the transcription factor activity associated with interferon and pathogen-associated molecular pattern (PAMP) receptors (Stat1, IRF3, and IRF7) was observed early (day 1 to 3 p.e.) during infection, while the activation of NF-B/REL, activator protein 1 (AP-1), and C/EBP, which are associated with regulating the production of inflammatory mediators in immune cells (31), showed a later upregulation (day 5 to 7 p.e. ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to their classical functions, these professional phagocytes also generate a host of cytokines and chemokines that condition the progression of the inflammatory reaction and the subsequent onset of an immune response (1-4). We and others have shown that the production of inflammatory cytokines by neutrophils involves various signaling pathways, including the p38 MAPK, MEK/ERK, PI3K, and IKK/IkB cascades (5)(6)(7)(8), leading to transcriptional activation, in good part via members of the NF-kB and C/EBP families of transcription factors (5,7,9). By contrast, the JNK/AP-1 axis does not seem to contribute to cytokine production in neutrophils (7,10,11).…”
mentioning
confidence: 99%